Sub-chronic testosterone treatment increases the levels of epithelial sodium channel (ENaC)-α, β and γ in the kidney of orchidectomized adult male Sprague–Dawley rats - Su Yi Loh; Nelli Giribabu; Naguib Salleh (PeerJ, 2016)
Testosterone has been reported to cause blood pressure to increase. However mechanisms that underlie the effect of this hormone on this physiological parameter are currently not well understood. The aims of this study were to investigate effects of testosterone on expression of α, β and γ-epithelial sodium channel (ENaC) proteins and messenger RNAs (mRNAs) in kidneys, the channel known to be involved in Na+ reabsorption, which subsequently can affect the blood pressure. Methods. Adult male Sprague–Dawley (SD) rats were orchidectomized fourteen days prior to receiving seven days treatment with testosterone propionate (125 µg/kg/day or 250 µg/kg/day) with or without flutamide (androgen receptor blocker) or finasteride (5α-reductase inhibitor). Following sacrifice, the kidneys were removed and were subjected for α, β and γ-ENaC protein and mRNA expression analyses by Western blotting and Real-time PCR (qPCR) respectively. The distribution of α, β and γ-ENaC proteins in kidneys were observed by immunofluorescence. Results. The α, β and γ-ENaC proteins and mRNA levels in kidneys were enhanced in rats which received testosterone-only treatment. In these rats, α, β and γ-ENaC proteins were distributed in the distal tubules and collecting ducts of the nephrons. Co-treatment with flutamide or finasteride resulted in the levels of α, β and γ-ENaC proteins and mRNAs in kidneys to decrease. In conclusions, increases in α, β and γ-ENaC protein and mRNA levels in kidneys mainly in the distal tubules and collecting ducts under testosterone influence might lead to enhance Na+ reabsorption which subsequently might cause an increase in blood pressure.